Potential areas of evergreen forests in Castile and Leon (Spain) according to future climate change - Del Río, Sara; ngel Penas, Á (Phytocoenologia, 2006)
Areas that may potentially be occupied by evergreen forests represent approximately 47% of the total area of the Castile and Leon region. This type of vegetation includes holm-oak (Quercus rotundifolia) and white juniper (Juniperus thurifera) forests. Both of them belong to eight different vegetation series.Considering the observed trends in annual mean temperature and precipitation in Castile and Leon for a thirty-seven-year period (1961?1997), three different hypotheses are put forward in this work to account for climate variations over periods of 25, 50 and 75 years and thus determine the changes that might occur in the areas suited to occupation by evergreen forests.This study also emphasizes the relevance of bioclimatic models for anticipating possible changes in the potential natural vegetation of a territory because of the influence of these changes on land use, conservation and management.Overall, our data support the concept that a decrease in Quercus rotundifolia and Juniperus thurifera forests could occur in Castile and Leon in the near future if the temperature and precipitation trends observed during recent years would remain constant. The main trends indicate an increase in the temperature of winter and decreases in summer. As far as precipitation is concerned, there is an increase in summer and decreases in winter. We conclude that these types of forest may be replaced by deciduous formations.
Keywords: bioclimatology; climactic dominion; climate change; evergreen forests

Potential areas of evergreen forests in Castile and Leon (Spain) according to future climate change - Del Río, Sara; ngel Penas, Á (Phytocoenologia, 2006)
Areas that may potentially be occupied by evergreen forests represent approximately 47% of the total area of the Castile and Leon region. This type of vegetation includes holm-oak (Quercus rotundifolia) and white juniper (Juniperus thurifera) forests. Both of them belong to eight different vegetation series.Considering the observed trends in annual mean temperature and precipitation in Castile and Leon for a thirty-seven-year period (1961?1997), three different hypotheses are put forward in this work to account for climate variations over periods of 25, 50 and 75 years and thus determine the changes that might occur in the areas suited to occupation by evergreen forests.This study also emphasizes the relevance of bioclimatic models for anticipating possible changes in the potential natural vegetation of a territory because of the influence of these changes on land use, conservation and management.Overall, our data support the concept that a decrease in Quercus rotundifolia and Juniperus thurifera forests could occur in Castile and Leon in the near future if the temperature and precipitation trends observed during recent years would remain constant. The main trends indicate an increase in the temperature of winter and decreases in summer. As far as precipitation is concerned, there is an increase in summer and decreases in winter. We conclude that these types of forest may be replaced by deciduous formations.
The following values have no corresponding Zotero field: pub-location: Stuttgart publisher: Schweizerbart'sche Verlagsbuchhandlung
Keywords: bioclimatology; climactic dominion; climate change; evergreen forests

Relation between climate and vegetation along a Mediterranean-Temperate boundary in central Italy - Blasi, C; Carranza, M L; Filesi, L; Tilia, A; Acosta, A (Global Ecology and Biogeography, 1999)
The relationship between climate and vegetation was investigated along a Mediterranean-Temperate boundary in central Italy. The study area is a transition zone between the Temperate (Eurosiberian) and Mediterranean regions and has an altitudinal range of almost 1750 m. Ordination and cluster analysis were used. The results did not show any sharp boundary but a climate-vegetation mosaic ranging from upper mountain thermotype and lower hyperhumid ombrotype with Fagus sylvatica L. woodlands at higher altitudes, to meso-Mediterranean thermotype and lower subhumid ombrotype with Mediterranean maquis and Quercus ilex L. woods on the coast. Six phytoclimatic groups are distinguished and described in terms of climatic parameters, vegetation types and morphological and chorological traits. These parameters indicate a change without sharp discontinuities between groups. The Mediterranean to Temperate transition in this Tyrrhenian sector is broad and includes most of the study area.
Keywords: bioclimatology; climatic indices; Mediterranean vegetation; phytoclimatic groups; temperate woodlands; transition areas

Relation between climate and vegetation along a Mediterranean-Temperate boundary in central Italy - Blasi, C.; Carranza, M. L.; Filesi, L.; Tilia, A.; Acosta, A. (Global Ecology and Biogeography, 1999)
The relationship between climate and vegetation was investigated along a Mediterranean-Temperate boundary in central Italy. The study area is a transition zone between the Temperate (Eurosiberian) and Mediterranean regions and has an altitudinal range of almost 1750 m. Ordination and cluster analysis were used. The results did not show any sharp boundary but a climate-vegetation mosaic ranging from upper mountain thermotype and lower hyperhumid ombrotype with Fagus sylvatica L. woodlands at higher altitudes, to meso-Mediterranean thermotype and lower subhumid ombrotype with Mediterranean maquis and Quercus ilex L. woods on the coast. Six phytoclimatic groups are distinguished and described in terms of climatic parameters, vegetation types and morphological and chorological traits. These parameters indicate a change without sharp discontinuities between groups. The Mediterranean to Temperate transition in this Tyrrhenian sector is broad and includes most of the study area.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: bioclimatology; climatic indices; Mediterranean vegetation; phytoclimatic groups; temperate woodlands; transition areas

Crecimiento radial del corcho de reproducción de los alcornocales catalanes y valencianos - Fos, S.; Barreno, E. (Scientia gerundensis, 1994)
Eastern cork-oak forests are present in territories with different environmental characteristics, allowing to raise comparative studies between them. This work is an attempt to evaluate the radial growt differences of the reproduction cork, using tschniques of optical microscopy, having developed a new methodology. Thus, severa1 sites from catalonian and valencian cork-oak forests have been selected. In the quantification of this growth, the contribution of each cork type (early cork and late cork) in the annual growing rings have been differentia- ted. The annual increments measwed in catalonian corks have an average of 2.958 mm, being a bit lower in Castell6n with 1.622 mm. These differences in the annual growing rings are due to the early development higher in catalonian cork (2.623 mm) than in valencian ones (1.235 mm), late cork thickness is similar in the two areas. These differences seem to be related with the escarce summer dry period in catalonian cork-oak forests. Important anato- mical differences related with the mentioned ombroclimatic asimetries have been observed too.
Keywords: Anatomy; bioclimatology; cork-oak; Quercus suber L.; Radial growth

Crecimiento radial del corcho de reproducción de los alcornocales catalanes y valencianos - Fos, S; BARRENO, E (Scientia gerundensis, 1994)
Eastern cork-oak forests are present in territories with different environmental characteristics, allowing to raise comparative studies between them. This work is an attempt to evaluate the radial growt differences of the reproduction cork, using tschniques of optical microscopy, having developed a new methodology. Thus, severa1 sites from catalonian and valencian cork-oak forests have been selected. In the quantification of this growth, the contribution of each cork type (early cork and late cork) in the annual growing rings have been differentia- ted. The annual increments measwed in catalonian corks have an average of 2.958 mm, being a bit lower in Castell6n with 1.622 mm. These differences in the annual growing rings are due to the early development higher in catalonian cork (2.623 mm) than in valencian ones (1.235 mm), late cork thickness is similar in the two areas. These differences seem to be related with the escarce summer dry period in catalonian cork-oak forests. Important anato- mical differences related with the mentioned ombroclimatic asimetries have been observed too.
Keywords: Anatomy; bioclimatology; cork-oak; Quercus suber L.; Radial growth